Expanding the indications of robotic surgery in urology: A systematic review of the literature - Raj P. Pal (Taylor & Francis Group, 2018)
Objectives: To evaluate the recent developments in robotic urological surgery, as the introduction of robotic technology has overcome many of the difficulties of pure laparoscopic surgery enabling surgeons to perform complex minimally invasive procedures with a shorter learning curve. Robot-assisted surgery (RAS) is now offered as the standard for various surgical procedures across multiple specialities. Methods: A systematic search of MEDLINE, PubMed and EMBASE databases was performed to identify studies evaluating robot-assisted simple prostatectomy, salvage radical prostatectomy, surgery for urolithiasis, distal ureteric reconstruction, retroperitoneal lymph node dissection, augmentation ileocystoplasty, and artificial urinary sphincter insertion. Article titles, abstracts, and full text manuscripts were screened to identify relevant studies, which then underwent data extraction and analysis. Results: In all, 72 studies evaluating the above techniques were identified. Almost all studies were retrospective single-arm case series. RAS appears to be associated with reduced morbidity, less blood loss, reduced length of stay, and comparable clinical outcomes in comparison to the corresponding open procedures, whilst having a shorter operative duration and learning curve compared to the equivalent laparoscopic techniques. Conclusion: Emerging data demonstrate that the breadth and complexity of urological procedures performed using the da Vinci® platform (Intuitive Surgical Inc., Sunnyvale, CA, USA) is continually expanding. There is a gaining consensus that RAS is producing promising surgical results in a wide range of procedures. A major limitation of the current literature is the sparsity of comparative trials evaluating these procedures. Keywords: Robot-assisted surgery, Robotic surgery, Urology